Preparation and Property of Carbon Nanofibers-reinforced Sm2O3-added Epoxy Resin Neutron Shielding Material - ZHAI Yutao1, WANG Hongqing1, 2, HUANG Qunying1 (Yuanzineng kexue jishu)
Small nuclear reactors have become one of the promising directions for the future development of advanced nuclear energy system due to its advantages of high safety, good economy, small-size flexibility, multi-purpose and modular construction. Moreover, the miniaturization of advanced nuclear reactor has imposed higher demands and big challenges to the nuclear radiation shielding system, and the traditional shielding materials are difficult to meet the new requirements for small nuclear energy systems on advanced neutron shielding material with light weight, high temperature resistance and good mechanical properties. In this study, a high temperature-resistant polymer neutron shielding composite CNFs/Sm2O3/AFG-90H was prepared by surface modification and high temperature vacuum curing methods with high temperature-resistant epoxy resin N,N-diglycidyl-4-glycidyl aniline (AFG-90H) as matrix, rare earth samarium oxide (Sm2O3) powders as neutron absorber, and carbon nanofibers (CNFs) as reinforced element in the composite. The effect of different CNFs mass fractions, such as 0.1%, 0.3% and 0.5%, on the mechanical properties, high temperature thermal properties and neutron shielding properties of the 15% Sm2O3/AFG-90H composite was studied. The results show that the size and interface effect of Sm2O3 particles and the entanglement of matrix molecular chains can inhibit the slide of polymer chains during the tensile process, which improves the mechanical and thermal properties of the composite. Moreover, when the contents of Sm2O3 and CNFs are 15% and 0.1%, respectively, the temperature for 5% thermal weight loss of the composite is 320.7 ℃, the tensile strength and elongation are 38.62 MPa and 0.9%, respectively, which are 82.3% and 63.0% higher than those of Sm2O3/AFG-90H. The strength and toughness of CNFs/Sm2O3/AFG-90H composite are significantly improved. When the CNFs contents are 0.1%-0.3%, CNFs can form a more effective heat transfer structure in the resin matrix to conduct heat in time, which is beneficial to avoid the composite decomposition caused by local heat accumulation, and increase the thermal conductivity and thermal stability of the composite. However, due to the high surface energy of CNFs, when the CNFs content is 0.5%, it is easy to unevenly distribute, stack or agglomerate in AFG-90H matrix and scatter the sound transport together with other defects and impurities, then the initial decomposition temperature and thermal stability of CNFs/Sm2O3/AFG-90H composite are negatively affected. The neutron shielding property of CNFs/Sm2O3/AFG-90H composite is mainly contributed by Sm2O3. The linear attenuation coefficient (LAC) of the Sm2O3/AFG-90H composite is the highest of 5.610 cm−1 without CNFs addition, which is 3.15 times higher than that of AFG-90H matrix. However, when the CNFs contents are 0.1%, 0.3% and 0.5%, respectively, the LAC of the CNFs/Sm2O3/AFG-90H composite is much higher than that of AFG-90H matrix. While the CNFs contents are no more than 0.3%, the surface energy effect of CNFs is not obvious. The distribution of Sm2O3 is less affected by the small addition of CNFs, and it can be considered that Sm2O3 still maintains a uniform distribution. Therefore, the LAC of CNFs/Sm2O3/AFG-90H composite is slightly lower than that of Sm2O3/AFG-90H composite. However, when the CNFs content is more than 0.5%, the surface energy interactions of CNFs become significant, and the local stacking or agglomeration of CNFs with the adsorption of Sm2O3 particles is easily produced during the preparation process of CNFs/Sm2O3/AFG-90H composite, which results in the non-uniform distribution of Sm2O3 particles and then may decrease the neutron shielding property of the composite. This study will provide some reference and guidance for the design, mechanical properties optimization and development of neutron shielding materials in the nuclear radiation protection system.